Proceeding of the fifth Southeast Asian ergonomics society conference on human factors vision - care for the future - Southeast Asian Ergonomics Society Conference on Human Factors Vision - Care for the Future (5th : 1997 : Kuala Lumpur, Malaysia); Halimahtun M. Khalid (Sarawak : UNIMAS, 1997)
PSZJBL